POETICS OF LANDSCAPE IN GARY SNYDER AND JACK SPICER’S POEMS: EVOKING ONE’S SENSE OF TIME AND PLACE IN A POST-TRUTH ERA OF ANTHROPOCENE - Yulianto, Henrikus Joko (Universitas Negeri Semarang, 2020)
Poetry should not only be dulce but also utile or being sweet and useful as what a Latin poet Horatius once said. The essence of usefulness is very indispensable in this recent post-truth era when the surging digital technology has contributed to the an escalating anthropocentric culture. Consumerism and other anthropogenic activities that pervade human daily life are the very epitome of this anthropocentrism. An obvious impact but also a polemical controversy of these practices is global warming as one ecological phenomenon. Ecopoetry as a sub-genre of environmental humanities or ecocriticism aims to unveil the truth that the biotic community consists of the interdependent relation between human and nonhuman animals and their physical environment. This ecological fact is an indisputable truth that differs from the one of social or political facts. Gary Snyder and Jack Spicer as two poets of the San Francisco Renaissance movement in the 1950s are two figures who show concern about human interconnection with material phenomena. In their succinct poems, they open one’s awareness that any material good is not an object but that each material thing co-exists with one’s consciousness in certain time and place. Their landscape poetics then is able to evoke one’s understanding of his/her interconnection with any life form in the natural world. This ecological awareness would impact on human savvy ways in consuming goods to fulfill daily necessities.